Conservation of forest species: a study in homegardens in Municipality of Cáceres –MT - Pereira, Paulo Vinícius Miranda; Figueiredo Neto, Leonardo Francisco (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Agroforestry System (AFS) are providing restoration alternatives anthropogenic environments. These systems are forms of cropsthat are associated, in the same area, trees and shrubs with crops or animals, simultaneously or staggered manner over time. One of the oldest agroforestry land use are the homegardens characterized by an imitation of natural ecosystems. It was accomplished a study of seven homegardens urban of the city of Cáceres-MT, tends as objective evaluates the contribution of the homegardens in the conservation of native and exotic forest species and your socioeconomic impact. The research was conducted through semi-structured interviews, associated with the techniques of "snowball" complemented by guided tour (floristic identification). Was recorded 51 species belonging to 41 genera and 27 families, especially families Arecaceae(7 spp.), Rutaceae(6 spp.), Anacardiaceae(5 spp.) and Myrtaceae(5 spp.). The native species were very common in homegardens, which may be indicative of sustainable use of biodiversity, reducing the pressure on the local vegetation. The species Mangifera indica(Mango), Annona squamosal(Minutes)and Malpighia glabra(Acerola)were found in all areas surveyed and has a consensus as to their use, contributing thus to the conservation of local biodiversity.